Durability of Expanded Physician Assistant Training Positions Following the End of Health Resources and Services Administration Expansion of Physician Assistant Training Funding. Issue 3 (September 2016) - Rolls, Joanne; Keahey, David
Abstract : Purpose: The purpose of this study was to assess the number of Health Resources and Services Administration Expansion of Physician Assistant Training (EPAT)-funded physician assistant (PA) programs planning to maintain class size at expanded levels after grant funds expire and to report proposed financing methods. The 5-year EPAT grant expired in 2015, and the effect of this funding on creating a durable expansion of PA training seats has not yet been investigated. Methods: The study used an anonymous, 9-question, Web-based survey sent to the program directors at each of the PA programs that received EPAT funding. Data were analyzed in Excel and using SAS statistical analysis software for both simple percentages and for Fisher's exact test. Results: The survey response rate was 81.48%. Eighty-two percent of responding programs indicated that they planned to maintain all expanded positions. Fourteen percent will revert to their previous student class size, and 4% will maintain a portion of the expanded positions. A majority of the 18 programs (66%) maintaining all EPAT seats will be funded by tuition pass-through, and one program (6%) will increase tuition. There was no statistical association between the program type and the decision to maintain expanded positions ( P = .820). Conclusions: This study demonstrates that the one-time EPAT PA grant funding opportunity created a durable expansion in PA training seats. Future research should focus on the effectiveness of the program in increasing the number of graduates choosing to practice in primary care and the durability of expansion several years after funding expiration.